The diatom test for drowning: an unreported source of diatom contamination - Lunetta, Philippe; Virri, Johanna; Weckström, Jan (Springer Science and Business Media LLC, 2026)
We describe here a previously unreported source of diatom contamination that may prove relevant in routine diatom analysis in suspected drowning cases. Glass microscope slides utilized in the process, during their manufacture, undergo a washing process, after which, diatomaceous earth (kieselguhr, fossil diatoms) is added to avoid producing stuck slides during the last rinse. The diatomaceous earth can be removed at this point only by means of aggressive cleaning, but the possibility exists that some fossil diatoms will remain on the slides. This potential contamination source explained a recurrent and otherwise puzzling appearance of Aulacoseira diatom genus in samples both from definite drowning cases and from non-drowned control cases. Discrimination by expert diatomologists between present-day fresh diatoms and fossil diatoms, together with awareness of the ubiquity of diatoms in nature and of their extensive use in the manufacturing industry, corroborate our view that potential sources of laboratory contamination should not be a rational impediment to performing diatom tests.